Odpisy aktualizujące wartość należności a podatek dochodowy - Orzeszko, Teresa (Write-Offs Updating the Value of Accounts Receivable vs. Income Tax, 2006)
The objective of the hereby article is an analysis of regulations in force in Poland referring to income tax in the context of relations occurring between the effective and reversed write-offs updating the value of accounts receivable vs. costs and proceeds set following the income tax requirements. As a result of conducted research it was observed as follows: « the notion of write-offs updating the value of accounts receivable has not been defined in Polish legislation, however their context points to the fact that they should be connected with the phenomenon of assets' book value correction due to changes in their real value in time, some categories of write-offs updating the value of accounts receivable are referred to as reserves, which should be regarded as a lack of order in Polish legislative terminology, tax law regulations referring to write-offs updating the value of accounts are not uniform, which means that the principles of including particular categories of write-offs to costs and tax proceeds are different.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (4); 2006; nr 1119, s. 123-142